Analisis Tingkat Kesejahteraan Ekonomi Rumah Tangga Petani Karet Rakyat di Kecamatan Bati – Bati, Kabupaten Tanah Laut - Nurhidayat, Rahmat; Maulina, Dessy (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the level of economic welfare of smallholder rubber farmers in Bati-bati District using Farmer Household Income Exchange Rate (NTPRP) analysis and analyze the factors that affect the level of economic welfare of smallholder rubber farmers consisting of land area, production amount, and price rubber either partially or simultaneously using multiple linear regression analysis. This research is descriptive, quantitative, and inferential. The location of the research was carried out in several villages in Bati-bati District with 40 farmers as respondents where the sampling used purposive sampling technique. The results showed that smallholder rubber farmers in the study area were classified as not prosperous where the results of the calculation of the Farmer's Household Income Exchange Rate < 1,00 (0.99 < 1,00). The land area, production amount, and rubber price either partially or simultaneously have a positive and significant effect on the Farmer's Household Income Exchange Rate (NTPRP) or the welfare level of smallholder rubber farmers.